Pengaruh Live Streaming, Cash On Delivery (COD), dan Promo Gratis Ongkir Terhadap Keputusan Pembelian pada Shopee - Fitriani Iskandar; Edi Maszudi; Samsinar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of live streaming, cash on delivery (COD) and free postage promos on purchasing decisions on Shopee. The population consists of Shopee application users in Palopo City. Research uses a quantitative approach. The sample in this study was obtained using the Conchran formula, determining the minimum sample number of 10 times the number of measurement items. The study used 20 indicators, so that the minimum number of samples was obtained (10 x 20 = 200). Data analysis techniques using SPSS 25. Then analyzed using multiple linear regression methods. Hypothesis testing with the F test to measure simultaneously and t tests to partially measure.